Transient Brittle Creep Mechanism Explains Early Postseismic Phase of the 2011 Tohoku‐Oki Megathrust Earthquake: Observations by High‐Rate GPS Solutions. Issue 8 (9th August 2022) - Periollat, Axel; Radiguet, Mathilde; Weiss, Jérôme; Twardzik, Cédric; Amitrano, David; Cotte, Nathalie; Marill, Lou; Socquet, Anne
Abstract: The early stage of the postseismic phase is characterized by a large deformation rate. Its analysis is thus key to decipher the role played by different mechanisms (afterslip and viscoelasticity) at various time scales. Here, we process GPS data to obtain 30‐s kinematic position time series recording the surface deformation following the M w 9.0 Tohoku‐Oki megathrust earthquake (2011), and combine them with static solutions over 9 years. We analyze the temporal evolution of the time series and use these observations to image the postseismic slip. We find that the first month of deformation following Tohoku‐Oki can be explained by an afterslip mechanism, that exhibits an "Omori‐like" decay, with a p ‐value around 0.75 almost everywhere with the exception of a small region around Ibaraki prefecture where p  ∼ 1 is observed. This p  < 1 indicates that the postseismic displacements do not increase logarithmically with time as predicted by rate‐and‐state rheology. Instead, we argue that early afterslip is associated with a transient brittle creep mechanism. We use numerical simulations to show that an exponent of p  < 1 can be explained by a combination of thermal activation of local slips and elastic interactions. Over longer time scales, an additional mechanism is required to explain the observed deformation signal, and the transient brittle creep mechanism is combined with viscoelastic relaxation modeled by a Newtonian flow. The spatial analysis reveals two distinct afterslip regions, a major one on the North, associated with a p ‐value around 0.75, and a smaller one close to the Ibaraki aftershock, associated with p  ∼ 1. Plain Language Summary: The Tohoku‐Oki earthquake of 11 March 2011, is the largest subduction earthquake of the past decade. Earthquakes produce a perturbation in the state of stress of the crust and mantle, and this perturbation is relaxed after the earthquake, during the postseismic phase. This phase is associated with deformations measurable at the earth surface with instruments such as GPS stations. Two main mechanisms are commonly considered to explain this postseismic phase: afterslip, which corresponds to the aseismic slip occurring around the fault zone, or a viscoelastic relaxation in the mantle. The originality of our study is the inclusion of the GPS signal from the first few minutes after the earthquake, giving details on the early postseismic deformation. We find that the early postseismic phase of Tohoku‐Oki can be understood from a different physical model than those commonly considered. Based on a spatial analysis, we have identified a first major afterslip region downdip of the Tohoku‐Oki rupture zone and a second small area near the largest aftershock. These two regions also show different temporal evolutions. Further studies on other large earthquakes should allow to revisit the early postseismic phase of large subduction earthquakes. Key Points: Kinematic and static positions time series are used to analyze the postseismic deformation following the M w 9.0 Tohoku‐Oki earthquake The temporal evolution of the early postseismic is explained by an Omori‐like Transient Brittle Creep mechanism with a p ‐value around 0.75 The spatial analysis reveals a major afterslip zone downdip from the main rupture and a secondary one close to the Ibaraki‐Oki event